Guthlac at Medeshamstede?. Issue 2 (30th March 2023) - Everson, Paul; Stocker, David
Abstract : This paper proposes that the early monastery at Medeshamstede (later Peterborough) was the sponsor and supporter of the hermit saint, Guthlac, on the fenland island of Crowland. It locates that initiative in the early Benedictine practice in England. It is argued that Medeshamstede subsequently sustained the saint's pre‐Viking cult, and is the best candidate for the location where Felix produced the saint's Life. The potential impact of this proposition on received understandings of the relationships between the monasteries of Medeshamstede and Ely and the kingdoms of Mercia and East Anglia – played out through the local polity of the Gyrwe – is noted. Early stone sculpture at Fletton is interrogated as potential evidence for the cult of Guthlac at Medeshamstede but found wanting.